Developmental trajectory of magnetic susceptibility in the healthy rhesus macaque brain. (14th May 2022) - Wu, Jing; Peng, Siyue; Zhang, Yuhua; Pan, Boyang; Chen, Honghua; Hu, Xintian; Gong, Nan‐Jie
Abstract : Quantitative susceptibility mapping (QSM) is used to quantify iron deposition in non‐human primates in our study. Although QSM has many applications in detecting iron deposits in the human brain, including the distribution of iron deposits in specific brain regions, the change of iron deposition with aging, and the comparison of iron deposits between diseased groups and healthy controls, few studies have applied QSM to non‐human primates, while most animal brain experiments focus on biochemical and anatomical results instead of non‐invasive experiments. Additionally, brain imaging in children's research is difficult, but can be substituted using young rhesus monkeys, which are very similar to humans, as research animals. Therefore, understanding the relationship between iron deposition and age in rhesus macaques' brains can offer insights into both the developmental trajectory of magnetic susceptibility in the animal model and the correlated evidence in children's research. Twenty‐three healthy rhesus macaque monkeys (23 ± 7.85 years, range 2–29 years) were included in this research. Seven regions of interest (ROIs—globus pallidus, substantia nigra, dentate nucleus, caudate nucleus, putamen, thalamus, red nucleus) have been analyzed in terms of QSM and R 2 * (apparent relaxation rate). Susceptibility in most ROIs correlated significantly with the growth of age, similarly to the results for R 2 *, but showed different trends in the thalamus and red nucleus, which may be caused by the different sensitivities of myelination and iron deposition in R 2 * and QSM analysis. By assessing the correlation between iron content and age in healthy rhesus macaques' brains using QSM, we provide a piece of pilot information on normality for advanced animal disease models. Meanwhile, this study also could serve as the normative basis for further clinical studies using QSM for iron content quantification. Due to the comparison of the susceptibility on the same experimental objects, this research can also provide practical support for future research on characteristics for QSM and R 2 *. Abstract : Seven ROIs in susceptibility maps and R 2 * from 3D five‐echo GRE MRI of 23 healthy rhesus macaque monkeys were analyzed to investigate the change of iron content with age in the brains. Susceptibility in most ROIs correlated significantly with increasing age, similarly to the results for R 2 *.